2011
DOI: 10.1113/expphysiol.2010.056713
|View full text |Cite
|
Sign up to set email alerts
|

The role of branched fibres in the pathogenesis of Duchenne muscular dystrophy

Abstract: Branched fibres are a well-documented phenomenon of regenerating skeletal muscle. They are found in the muscles of boys with Duchenne muscular dystrophy (DMD), a severe condition of progressive muscle wasting caused by an absence of the sarcolemmal protein dystrophin, and in the muscles of the mdx mouse, an animal model of DMD. However, only a handful of studies have investigated how the physiological properties of these morphologically deformed fibres differ from those of normal fibres. These studies have fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
88
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 48 publications
18
88
1
Order By: Relevance
“…Increased branching of myofibers has been reported in DMD patients, in embryonic and adult mdx mice and in mice lacking the olfactory receptor MOR23 or the intermediate filament desmin [44][45][46][47] . In adult mdx mice, increased branching has been proposed to result from abnormal fiber morphogenesis caused by defective myoblast fusion arising during the regeneration process stimulated by fiber degeneration 36,45,47 . However, the increased branching of mdx fibers differentiated from ES cells in vitro was unexpected as such a phenotype has not been reported in primary mdx myoblast cultures or in human DMD myoblast cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Increased branching of myofibers has been reported in DMD patients, in embryonic and adult mdx mice and in mice lacking the olfactory receptor MOR23 or the intermediate filament desmin [44][45][46][47] . In adult mdx mice, increased branching has been proposed to result from abnormal fiber morphogenesis caused by defective myoblast fusion arising during the regeneration process stimulated by fiber degeneration 36,45,47 . However, the increased branching of mdx fibers differentiated from ES cells in vitro was unexpected as such a phenotype has not been reported in primary mdx myoblast cultures or in human DMD myoblast cultures.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a key element of Ca 2ϩ signaling within the junctional membranes and may be a major part of STIM1 signaling in muscle development (30). In dystrophic muscle, these changed levels of Ca 2ϩ signaling proteins and therefore the reshaped signals may be a critical link in attempts at initiating fiber regeneration in dystrophic muscle (4,17). STIM1-POST also regulates other key proteins such as Na ϩ -K ϩ -ATPase and SERCA (18).…”
Section: Stim1 Isoforms In Musclementioning
confidence: 97%
“…Moreover, myofibers differentiated from Dag1 null mESCs exhibit defects in the assembly of postsynaptic elements including acetylcholine receptor (AchR) clusters (Jacobson et al, 2001). Dmd mdx mPSC lines were shown to exhibit defects in myogenic differentiation and increased apoptosis , while Chal et al (2015) reported a branching defect characterized by an increased number of split fibers, a phenotype also seen in Duchenne muscular dystrophy (DMD) patients and the mdx mouse (Chan and Head, 2011). Finally, myoblasts derived from DMD human iPSCs were shown to exhibit fusion defects that could be corrected by dual inhibition of TGFβ and BMP signalings (Choi et al, 2016).…”
Section: Myofiber Maturation In Vitro Sarcomeres and Structural Assemblymentioning
confidence: 99%